A hybrid mutiresolution representation for fast tree modeling and rendering - Lluch, Javier; Camahort, Emilio; Hidalgo, Jose Luis; Vivo, Roberto (Procedia computer science, 2010)
We introduce a new representation for modeling and rendering plants and trees. The representation is multiresolution and can be automatically generated and rendered in an efficient way. For the trunk and branches we procedurally build a multiresolution structure that preserves the visual appearance of a tree, when rendered at different levels of detail. For the leaves we build a hierarchy of images by pre-processing the botanical tree structure. Unlike other representations, the visual quality of our representation does not depend on viewing position and direction. Our models can be applied to any computer graphics area that requires modeling outdoor scenes like interactive walkthroughs and fly-by’s, realistic rendering, simulation and computer games.